Growth and initial development of passion fruit plants in different concentrations of biostimulants - Mariane Sirqueira Nogueira; Sammy Sidney Rocha Matias; Thamyres Yara Lima Evangelista; Bruno Anderson Araújo Barros; Gustavo Alves Pereira; Gasparino Batista de Sousa (Comunicata Scientiae, 2021)
The objective of this research was to evaluate the vegetative growth of yellow passion fruit seedlings, propagated by seeds, regarding the rates of use and application of two biostimulants in two types of soil. The experiment was carried out at the State University of Piauí (UESPI) / Campus de Corrente, with Passiflora edulis as a research culture, on a 50% brightness screen. The completely randomized design consisted of four treatments arranged according to the following application doses (0, 4, 8, 12 and 16 mL), using the biostimulant Solofull® and Stimulate® via soil, with six replicates per treatment, totaling 24 units experimental. The soil used came from two situations, soil 1 (area in the process of degradation, Gilbués - PI) and soil 2 (pasture area, Corrente, PI). At 65 days after sowing, height, stem diameter, number of true leaves, leaf area, plant height ratio and stem diameter and root length were evaluated. The data were submitted to analysis of variance. The application of the Stimulate® biostimulant in seedlings produced in soil cultivated by pasture, promoted the best development of the aerial and root system of the plants.